A multilayer-graphene nanosheet film deposited on a ceramic substrate without a catalyst for constructing an electrochemiluminescence imaging platform. Issue 25 (14th June 2019) - Wang, Jiannan; Shang, Pengxiang; Zhong, Jiangyan; Lin, Shan; Chi, Yuwu
Abstract : Without a catalyst, a multi-layer graphene nanosheet (MLGNS) film is deposited on a ceramic substrate by using ethanol as the carbon source. The MLGNS film/ceramic shows promising applications in electrochemistry. Abstract : Chemically and electrochemically stable conducting films are very desirable in the electrochemical industry and electrochemical sensing. In this work, ethanol was used as the carbon source to synthesize a multilayer-graphene nanosheet (MLGNS) film on ceramic substrates by a catalyst-free chemical vapor deposition (CVD) method at 900 °C and under ambient pressure. The developed CVD method is simple, economical and safe and avoids damage to the graphene nanosheet film during its transfer from the metal substrate to the non-metal substrate. The synthesized MLGNS film was well characterized by various techniques, including scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and Raman spectroscopy. The prepared MLGNS film has good chemical and electrochemical stability and satisfactory electrical conductivity thus can be used as a new type of electrode material. The MLGNS film on the ceramic substrate has been fabricated into an electrochemiluminescence (ECL) imaging platform to investigate the oxygen reduction reaction (ORR) and evaluate the activities of ORR catalysts, such as PtNPs. The established MLGNS film-based ECL imaging platform may have promising applications in the study of catalysts for fuel cells, high throughput immunoassay in the clinic, and fast screening of anti-cancer drugs.